Variation of absorbed radiation dose of wild boar living in the territory of radioactive contamination - Gulakov, Andrey V.; Drozdov, Denis N. (Journal of the Belarusian State University. Ecology, 2022)
The article presents the results of the assessment of the absorbed dose rate from incorporated radionuclides of 137Cs and 90Sr in the body of wild boar living in an area with different levels of radioactive contamination. The internal irradiation dose was evaluated for incorporated 137Cs in muscle and 90Sr in bone tissue of wild boar. During the assessment, it was assumed that radionuclides 137Cs uniformly distributed in the tissue and are in equilibrium conditions, and radionuclides are 90Sr concentrated in the bone tissue of the animal, during the year the concentration of radionuclides is assumed to be constant. In total, samples were obtained from 117 wild boar individuals, among which 87 animals were seized in the exclusion zone and 30 in the resettlement zone. From the animal carcass, spot samples of muscle tissue were taken according to 500 ± 50 g, the 137Cs content in the samples was determined for raw, natural mass. The activity of 90Sr in bone tissue was determined by radiochemical method.As a result of the studies, it was found that the average total exposure dose of wild boar seized in the exclusion zone is twice that of animals seized in the resettlement zone (p
Keywords: wild boar; muscle tissue; radioactive contamination; 137Cs; 90Sr; dose rate; Polessky State Radiation Ecological Reserve